WOMEN IN THE PERSPECTIVE OF THE PAKISTANI LABOR MARKET (Research Bulletins of the Faculty of Economic Sciences, 2022)
The main aim of the article is to assess the situation of women in the labor markets in Islamic countries, in particular their professional activity. The analyzes were based on the example of the labor market of the Islamic Republic of Pakistan 1973-2020. The main question that was tried was formulated as: whether the labor market in Pakistan is differentiated in terms of gender and, if so, what is the trend of changes in the economic activity of women. The subject of the analyzes are the basic characteristics describing the professional activity of women in a traditional way, ie the economic activity rate, the number and structure of employment, and the unemployment rate. The primary source of data is the database of the International Labor Organization and the database of the World Bank. The situation of women in the labor market of the Islamic Republic of Pakistan is difficult. Pakistan is the fifth largest country in the world in terms of population and the sixth largest labor force, with the labor force participation rate in 2019 - 52.51%. Pakistani women make up about half of the population, but they participate only to a small extent in the labor market. Professional activity of Pakistani women in the last five years has not exceeded 23%, which is one of the worst results in the world. Positive changes are taking place, but the process is very slow. The exclusion of women from the labor market entails costs for the economy and has a negative impact on its socio-economic development. The Pakistani government has set ambitious goals for the labor market, in which the increase in the professional activity of women plays a key role.
Keywords: labor force; labor market; gender; Pakistan